The determinant of expansion phases in business cycle impact on the performance of automotive company in Malaysia / Ummi Kalthum Othman - Othman, Ummi Kalthum (2011)
The automotive industry is one of the most important and strategic industries in the Malaysian manufacturing sector. Since the first national car, the Proton Saga, rolled out of its plant 1985, Malaysia has obtained much recognition regionally and internationally for its outstanding achievement in the automobile industry. The purpose of this paper is to identify what are the determinants (capital investment, size of company and company profit) of expansion phases in business cycle impact on the performance of automotive company in Malaysia. This study use many kind of journal, magazine and article as the evidence to collect that the expansion phases in business cycle have major impact to the automotive company performance. The empirical analysis use Proton Holding Bhd and Honda Motor Company as the sample to support the objective of the research. The performance both of the company from 2006-2010 are measured to get the consistence and right finding. For finding chapter, the issues along the 5 years and today current issues are more deeply interpretation in order to get the tally data compared with the evidence from literature review. In the future research should be analyze the other phases in business cycle that can impact on the automotive company performance.